Biochemical and genetic studies define the functions of methylthiotransferases in methanogenic and methanotrophic archaea - Boswinkle, Kaleb; Dinh, Thuc-Anh; Allen, Kylie D. (Frontiers in Microbiology, 2023)
Methylthiotransferases (MTTases) are radical S-adenosylmethionine (SAM) enzymes that catalyze the addition of a methylthio (-SCH3) group to an unreactive carbon center. These enzymes are responsible for the production of 2-methylthioadenosine (ms 2 A) derivatives found at position A37 of select tRNAs in all domains of life. Additionally, some bacteria contain the RimO MTTase that catalyzes the methylthiolation of the S12 ribosomal protein. Although the functions of MTTases in bacteria and eukaryotes have been established via detailed genetic and biochemical studies, MTTases from the archaeal domain of life are understudied and the substrate specificity determinants of MTTases remain unclear. Here, we report the in vitro enzymatic activities of an MTTase (C4B56_06395) from a thermophilic Ca. Methanophagales anaerobic methanotroph (ANME) as well as the MTTase from a hyperthermophilic methanogen -MJ0867 from Methanocaldococcus jannaschii. Both thermophilic archaeal MTTases catalyze the methylthiolation of N 6 -threonylcarbamoyladenosine (t 6 A) and N 6 -hydroxynorvalylcarbamoyladenosine (hn 6 A) residues to produce 2-methylthio-N 6threonylcarbamoyladenosine (ms 2 t 6 A) and 2-methylthio-N 6 -hydroxynorvalylcarbamoyladenosine (ms 2 hn 6 A), respectively. To further assess the function of archaeal MTTases, we analyzed select tRNA modifications in a model methanogen -Methanosarcina acetivorans -and generated a deletion of the MTTase-encoding gene (MA1153). We found that M. acetivorans produces ms 2 hn 6 A in exponential phase of growth, but does not produce ms 2 t 6 A in detectable amounts. Upon deletion of MA1153, the ms 2 A modification was absent, thus confirming the function of MtaBfamily MTTases in generating ms 2 hn 6 A modified nucleosides in select tRNAs.